Biodiesel production from waste cooking oil via supercritical methanol: Optimisation and reactor simulation. (August 2018) - Aboelazayem, Omar; Gadalla, Mamdouh; Saha, Basudeb
Abstract: Biodiesel production using supercritical methanol in the absence of catalyst has been analysed by studying the main factors affecting biodiesel yield. A quadratic polynomial model has been developed using Response Surface Methodology (RSM). Box-Behnken Design (BBD) has been used to evaluate the influence of four independent variables i.e. methanol to oil (M:O) molar ratio, temperature, pressure and time on biodiesel yield. The optimum biodiesel yield is 91% at M:O molar ratio, temperature, pressure and reaction time of 37:1, 253.5 °C, 198.5 bar and 14.8 min, respectively. Overall reaction kinetics has been studied at optimum conditions concluding a pseudo first order reaction with reaction rate constant of 0.0006s −1 . Moreover, thermodynamics of the reaction has been analysed in the temperature range between 240 and 280 °C concluding frequency factor and activation energy of 4.05s −1 and 50.5 kJ/mol, respectively. A kinetic reactor has been simulated on HYSYS using the obtained kinetic data resulting in 91.7% conversion of triglycerides (TG) with 0.2% relative error from the experimental results. Graphical abstract: Highlights: Study of overall transesterification reaction kinetics. Optimisation by Response Surface Methodology enhanced biodiesel yield. Simulation of kinetic reactor based on experimental data. Physiochemical properties of produced biodiesel showed good agreement with EN14214 standard.